2019
DOI: 10.1002/biof.1541
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for high‐density lipoproteins in neurodegenerative disorders

Abstract: Lipoproteins are the complexes of different lipids and proteins, which are devoted to the transport and clearance of lipids or lipid‐related molecules in the circulation. Lipoproteins have been found to play a crucial role in brain function and may influence myelination process. Among lipoproteins, high‐density lipoproteins (HDLs) and their major protein component, apoA‐I, are directly involved in cholesterol efflux in the brain. It has been suggested that inadequate or dysfunctional brain HDLs may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 192 publications
(394 reference statements)
1
20
0
Order By: Relevance
“…Small HDL-C particles are able to enter into the brain, and they also circulate in the peripheral blood. As the only lipoprotein in CSF, HDL has been found to regulate intracellular cholesterol homeostasis and amyloid protein metabolism in the brain (Bahrami et al, 2019). In this study, we identified that HDL-C levels were negatively associated with AD, which is consistent with the previous finding that higher levels of HDL may reduce the risk of the late-onset AD (Reitz et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Small HDL-C particles are able to enter into the brain, and they also circulate in the peripheral blood. As the only lipoprotein in CSF, HDL has been found to regulate intracellular cholesterol homeostasis and amyloid protein metabolism in the brain (Bahrami et al, 2019). In this study, we identified that HDL-C levels were negatively associated with AD, which is consistent with the previous finding that higher levels of HDL may reduce the risk of the late-onset AD (Reitz et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, decreased HDL-C levels may reduce the risk of cardiovascular and cerebrovascular diseases (CVD) as well as the development of AD or vascular dementia. Meanwhile, HDL-C deficiency had been identified to contribute to cognitive impairment by affecting the risk of atherosclerosis (Bahrami et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Underscoring the signalling potential of lipoproteins, low-density lipoproteins isolated from eCSF are responsible, to a significant extent, for neurogenic activity of the eCSF [148]. On the other hand, changed levels of high-density lipoproteins in CSF were linked to the pathophysiology of various neurodegenerative diseases [149]. In the recent years, several morphogens produced by the CPe were identified to associate directly with lipoproteins, including SHH [63,150], FGFs [98,151], or Wnts [62].…”
Section: Lipoprotein Complexes In Cp-csf Signallingmentioning
confidence: 99%
“…Heat stress affects intestinal bacterial composition [20] and damages intestinal barrier integrity, increasing intestinal permeability, "leaky gut" [21,22], and consequently leading to elevated systemic lipopolysaccharide (LPS) levels [23]. Toxemia further causes neuroinflammation with neurological disorders and related emotional and mental damage [24,25].…”
Section: Introductionmentioning
confidence: 99%